1996
DOI: 10.1038/bjc.1996.180
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between smoking exposure and p53 overexpression in colorectal cancer

Abstract: SummaryAlthough epidemiological studies of the relationship between cigarette smoking and colorectal cancer risk have been equivocal, a positive association is consistently found for colorectal adenoma development. We performed an epidemiological study to determine whether p53 protein overexpression, in tumours obtained at the time of resection, is associated with cigarette exposure in colorectal cancer. A total of 163 colorectal cancer cases and 326 healthy controls responded to a standardised questionnaire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 57 publications
1
8
0
4
Order By: Relevance
“…This association persisted when only examining CIS and IM cases compared to control and was robust to different definitions of p53 positivity. This finding also closely matches that of Freedman and colleagues in their case-control study of invasive colorectal cancer: OR = 1.84 (95% CI, 1.00–3.37) with heavy cigarette smoking (40+ pack years) for p53 negative colorectal cancer and no association with p53 positive colorectal cancer as determined by protein overexpression [26]. Our findings also lend support to recent findings by Slattery and colleagues on the association between cigarette smoking and microsatellite instability (MSI) positive invasive colon cancers (OR = 1.6, 95%CI = 1.0–2.5 for men, OR = 2.2, 95%CI = 1.4–3.5 for women) but not MSI negative cancers[27].…”
Section: Discussionsupporting
confidence: 88%
“…This association persisted when only examining CIS and IM cases compared to control and was robust to different definitions of p53 positivity. This finding also closely matches that of Freedman and colleagues in their case-control study of invasive colorectal cancer: OR = 1.84 (95% CI, 1.00–3.37) with heavy cigarette smoking (40+ pack years) for p53 negative colorectal cancer and no association with p53 positive colorectal cancer as determined by protein overexpression [26]. Our findings also lend support to recent findings by Slattery and colleagues on the association between cigarette smoking and microsatellite instability (MSI) positive invasive colon cancers (OR = 1.6, 95%CI = 1.0–2.5 for men, OR = 2.2, 95%CI = 1.4–3.5 for women) but not MSI negative cancers[27].…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis reported no association between GSTM1 null genotype and colorectal cancer [35]. Only a few GSTM1 previous studies also investigated the relationship between the GST polymorphisms and the effect of cigarette smoking on colorectal cancer [36][37][38][39][40][41]. However, these studies have been inconclusive.…”
Section: Introductionmentioning
confidence: 98%
“…Some dietary factors may be related to specific genetic alterations, such as mutations in the p53 tumor‐suppressor gene. Epidemiological studies have addressed risk‐factor patterns of colorectal carcinomas with and without p53 over‐expression (Zhang et al, 1995; Fredrikson et al, 1996; Freedman et al, 1996a,b,c). Interestingly, Freedman et al (1996 a ) found cruciferous vegetables to be protective among cases with p53‐positive tumors, but not in p53‐negative cases, as compared with controls.…”
mentioning
confidence: 99%